Accuracy of 99mTc-Hydroxymethylene diphosphonate scintigraphy for diagnosis of transthyretin cardiac amyloidosis - Cappelli, Francesco; Gallini, Chiara; Di Mario, Carlo; Costanzo, Egidio Natalino; Vaggelli, Luca; Tutino, Francesca; Ciaccio, Alfonso; Bartolini, Simone; Angelotti, Paola; Frusconi, Sabrina; Farsetti, Silvia; Vergaro, Giuseppe; et al. (Journal of nuclear cardiology, 2019)
Either 99mTechnetium diphosphonate (Tc-DPD) or pyrophosphate (Tc-PYP) scintigraphy plays a relevant role in diagnosing transthyretin cardiac amyloidosis (CA), and labeled radiotracers have been extensively studied in diagnosing CA. Few studies have analyzed and validated 99mTc-Hydroxymethylene diphosphonate (Tc-HMDP). Our aim was to validate the diagnostic accuracy of Tc-HMDP total-body scintigraphy in a cohort of patients with biopsy-proven transthyretin CA. We retrospectively evaluated all patients undergoing 99mTc-HMDP total-body scintigraphy, in adjunct to a comprehensive diagnostic work-up for suspected CA. Sixty-five patients were finally diagnosed with CA, while it was excluded in 20 subjects with left ventricular hypertrophy of various etiologies. Twenty-six patients had AL-CA, 39 had TTR CA (16 TTRm, 23 TTRwt). At Tc-HMDP scintigraphy, 2 AL patients showed a Perugini score grade 1 heart uptake, while 24 showed no uptake. All TTR patients showed Tc-HMDP uptake, with three patients showing a Perugini score grade 1, 16 grade 2, and 20 grade 3, respectively. No uptake was observed in patients with left ventricular hypertrophy. A positive Tc-HMDP scintigraphy showed a 100% sensitivity and a 96% specificity for TTR CA identification. Tc-HMDP scintigraphy is as accurate as Tc-DPD or Tc-PYP, and may therefore de facto be considered a valuable tool for the diagnosis of TTR CA.